Peningkatan Hasil Belajar Peserta Didik pada Pembelajaran Pendidikan Pancasila Menggunakan Model Game Based Learning di Kelas IV SD Negeri 02 Jambak Kabupaten Pasaman - Prameswari, Adiva Ayodia; Rahmatina, Rahmatina (ALSYS, 2024)
This research is motivated by the low learning outcomes of students and this condition is caused by the preparation of learning plans, teachers have not developed innovative and varied learning models according to the characteristics of students so that in the learning process students are less active and less enthusiastic. The aim of this research is to describe the improvement in student learning outcomes during Pancasila education learning using the game based learning model in class IV of SDN 02 Jambak, Pasaman Regency. This research is classroom action research that uses qualitative and quantitative approaches. Implemented in two cycles, namely cycle I consisting of 2 meetings and cycle II consisting of 1 meeting. Each cycle includes four stages, namely planning, implementation, observation and reflection. The subjects of this research were teachers and students of class IV SDN 02 Jambak with a total of 22 students and data collection techniques in the form of observation, tests and non-tests. The research results showed an increase in: a) Teaching modules in cycle I with an average of 82.5 (Good), and cycle II 96% (Very Good), b) Implementation in the teacher aspect of cycle I with an average of 83.5% (Good), and cycle II 95% (Very Good), while in the student aspect of cycle I with an average of 79% (Fair), and cycle II 92% (Very Good), c) The learning outcomes of students in cycle I obtained an average of 82 (Good) and cycle II with an average of 92 (Very Good). Based on these results, it can be concluded that using the game based learning model can improve student learning outcomes in Pancasila education learning.